Seasonal variation of amine-containing particles in urban Guangzhou, China. (1st February 2020) - Lian, Xiufeng; Zhang, Guohua; Lin, Qinhao; Liu, Fengxian; Peng, Long; Yang, Yuxiang; Fu, Yuzhen; Jiang, Feng; Bi, Xinhui; Chen, Duohong; Wang, Xinming; Peng, Ping'an; et al.
Abstract: Amines are ubiquitous in the environment and pose potential impacts on atmospheric chemistry; however, their seasonal variations and atmospheric processes remain unclear. In this study, a single-particle aerosol mass spectrometer is employed to investigate the seasonal variations of amine-containing particles as well as the oxidation of trimethylamine (TMA) in the urban region of Guangzhou, China. Number fractions of the amine-containing particles exhibit distinct seasonal variations, with higher fractions in spring and summer. Four amines, namely, TMA, diethylamine (DEA), dipropylamine, and tripropylamine are observed over all the seasons. DEA and TMA are the most dominant and account for approximately 90% of all these amine-containing particles. They are mainly clustered into eight types, comprised of internally mixed organics and elemental carbon (OCEC), OC–K, EC, Metal–rich, Dust, NaK–EC, Amine–rich, and high molecular weight organic compounds. DEA and TMA distribute differently over particle types and exhibit a distinct mixing state because of their different physicochemical properties. Compared with TMA, DEA is associated with more sulfate. The possible oxidation of TMA is also investigated, and the results indicate the potential contribution of aqueous oxidation or NO3 radical oxidation to the formation of TMA oxide. Overall, the results improve the comprehension of the formation and evolution processes of amines in atmospheric environment. Highlights: The number fraction of amine-containing particles in spring/summer is higher. Trimethylamine and diethylamine distribute differently over particle types. Compared with trimethylamine, diethylamine is associated with more sulfate. A large fraction of trimethylamine is observed to be oxidized mainly at night.